Some properties of Enterobacter Cloacae cultures isolated from sheeps - R. H. Gajrabekov; R. A. Achaev; E. S. Erzhapova; R. S. Erzhapova (Юг России: экология, развитие, 2015)
There were isolated 124 kinds of bacteria related to genus Enterobacteria, kind of Enterobacter. These isolated kinds were researched for having some facts of pathogenicity hemaglutinating ability as by D-mannosy, as by its absence, hematlogic ability, resistance to antibacterial prepirations. As a resalt were apparented that the more of strains have got traitsof pathogenisity and multiple resistance to antibiotics.